IBNU MADHĀ DAN REVOLUSI NAHWU ALA MADZHAB ANDALUSIA - Afnan Arummi (CMES (Center of Middle Eastern Studies), 2015)
This research is aimed to investigate the penetrations in Nahwu’s (Arabic Syntax) thoughts toward one of Nahwu’s school that was centered in Spain during the Islamic Caliph (Andalusia). One of the prominent figure in this era was Ibnu Madha. Thus, the problems in this research will be focused in some cases such as: (1) what is the revolutionary thoughts belong to Ibnu Madha in his work to develop the Arabic Syntax (Nahwu) based on Andalusia School? (2) what is the main reason that was underlaid by the thought of Ibnu Madha? To elaborate the answers of these cases, the researcher has used some approachs, such as the literature approach, then, to strengthen the data analysis descriptively, the researcher has used and pointed into the descriptive analysis method on behalf to find the conclusion in every single cases before finally doing the last conclusion comprehensively.